Rural Youth Entrepreneurs in East Africa: A view from Uganda and Kenya - Namatovu, Rebecca; Dawa, Samuel; Mulira, Fiona; Katongole, Celestine; Nyongesa, Stella (Investment Climate and Business Environment Research Fund (ICBE-RF), 2012)
This report is a result of a project titled Entrepreneurship empowering marginalized groups. The project was made possible through funding from the IDRC Trust Africa Investment Climate and Business Environment- Research Fund. The overall objective of the project was to explore the entrepreneurship initiatives that marginalized groups which included women, rural youth and the disabled are engaged in. From earlier studies it is evident that governments are aware of the looming youth problems especially the rising unemployment and entrepreneurship is being considered as a measure to mitigate the crisis. This report is intended to document the rural youth entrepreneurship situation in East Africa, the Ugandan and Kenyan contexts in particular, looking at why rural youth engage in entrepreneurship and what benefits arise there from. The report explores several facets of entrepreneurship as it compares rural youth activities and behaviors in Uganda and Kenya. It examines the socio economic environment in which these young people operate. Further, the report highlights the current policy gaps in youth entrepreneurship by exposing the unique challenges they face and assessing if the initiatives that have been devised have indeed worked. Proposals to achieve entrepreneurship for sustainable growth are then outlined.